Morphological Characterization and Genetic Analysis of Finger Millet (Eleusine coracana (L.) Gaertn) Germplasm - Negi, Shivangi; Kumar, Vineet; Bhatt, Arun (International Journal of Bio-resource and Stress Management, 2017)
The present investigation was conducted during kharif, 2014 at Research Block, Dept. of Crop Improvement, V.C.S.G. Uttarakhand University of Horticulture and Forestry, College of Forestry, Ranichauri Campus with thirty-five diverse genotypes of finger millet including three checks viz., PRM-1, PRM-2 and VL-149 laid out in Randomized Complete Block Design. Observations were recorded for fourteen morphological traits and the data were analyzed for variability, heritability and expected genetic advance. Computation of genotypic, phenotypic and environmental variances, genotypic coefficient of variance, phenotypic coefficient of variation and environmental coefficient of variation, heritability (in broad sense) and genetic advance were statistically worked out to understand the nature and extent of variability in expression of different characters prevailed in population and that led to facilitate selection for various traits for identifying desired genotyped suitable for hills. Analysis of variance revealed highly significant differences among all thirty-five genotypes with a wide range of mean values for different characters. There was sufficient variability found for all the characters among the various genotypes which could offer great scope for improvement. Genotypic and phenotypic variances were highest for biological yield per plant followed by plant height, days to 50 per cent flowering and harvest index. Hence, these characters are more suitable for selection procedure. High heritability coupled with high genetic advance was observed for biological yield per plant, plant height and days to 50 per cent flowering. Direct selection for these characters would be effective as heritability and genetic advance might be due to additive gene interaction.